COVID’s scholarly literature and innovation in startups - Gupta, V.; Gupta, C.; Peters, L.; Pereira, L. (Emerging technologies for innovation management in the software industry, 2022)
The importance of scholarly literature on startup capacities to stimulate innovation in pandemic times is highlighted in this chapter. The scholarly literature can help startups looking for opportunities or solutions in the face of a pandemic, but knowledge acquisition from secondary materials may be limited due to the growing number of publications, retractions, and preprints. The growing number of publications and venues makes it more difficult for entrepreneurs to get the information they need, analyse it, and then use collective intelligence to turn it into useful business knowledge. Retractions may steer startups in the incorrect direction, resulting in a waste of financial resources. Preprints are non-peer reviewed research articles that may provide some direction to startups but should not be relied upon entirely. The solutions to these issues are finally provided. Addressing these concerns could make scholarly literature beneficial to startups, allowing the global community to respond to the pandemic as a whole.